Association Between Obesity and Microvascular Diseases in Patients With Type 2 Diabetes Mellitus - Gao, Shan; Zhang, Hongliang; Long, Chen; Xing, Zhenhua (Frontiers in Endocrinology, 2021)
This study aimed to evaluate the association between obesity, evaluated by fat mass index (FMI)with the risk of microvascular diseases in patients withT2DM and compare the magnitude of associations of FMI, body mass index (BMI), and waist circumference (WC)with the risk of microvascular diseases We performed a post-hoc analysis of the Action to Control Cardiovascular Risk in Diabetes study. The primary microvascular outcomes of the present study included CKD (chronic kidney disease) progression, retinopathy, and neuropathy. Cox proportional-hazards models were preformed to evaluate the association evaluated FMI with microvascular diseases; discordant analysis to compare the magnitude of associations of FMI, body mass index (BMI), and waist circumference (WC)with the risk of microvascular diseases. Our study included 10,251 T2DM participants with a median 5 years (interquartile range 4·2-5·7) follow-up. 6,184 participants developed CKD progression, 896 participants had retinopathy, and 3,213 participants developed neuropathy (MNSI > 2·0). After confounding factors were adjusted for, patients in the highest FMI quartile had a higher risk of CKD progression ( HR: 1·26, 95%CI: 1·16–1·36), and neuropathy (HR: 1·93, 95% CI: 1·74–2·15), except for and retinopathy (HR: 1·17, 95% CI: 0·96–1·43) than those in the lowest quartile. Discordant analyses found FMI and WC are better in identifying individuals with obesity related risk of neuropathy, compared with BMI; neither is better in identifying individuals with obesity related risk of CKD progression and retinopathy. Obesity is statistically associated with CKD progression and neuropathy in T2DM participants. Further randomized trials are needed to test whether obesity control can improve the outcomes of T2DM participants with CKD or neuropathy. FMI and WC are better more useful in identifying individuals with obesity related risk of neuropathy compared with BMI in T2DM patients.